Increasing pulse agrobiodiversity to improve food security and sustainable agriculture in Sub-Saharan Africa - Ngigi, Peter Biu; Mouquet-Rivier, Claire; Amiot, Marie-Josèphe; Termote, Celine; Pallet, Dominique (Frontiers in Sustainable Food Systems, 2022)
Long-life cycle pulses have significant food security potential, however, there is little evidence to explain why they are not more widely produced and consumed in sub-Saharan Africa (SSA). This study aimed at exploring existing knowledge to inform on future research priorities in mainstreaming superior species. As staple food along with cereals, pulses are an important source of nutrients whose intake is often inadequate in SSA, however, pulse consumption remain inadequate in SSA. Depending on the crop’s life cycle, pulses have multiple functions that can support food systems and ecosystem resilience. Compared to short-life cycle pulses, long-life cycle pulses rank higher in multipurpose role. However, prior research has focused primarily on short-life cycle pulses due to rapid grain production. Long-life cycle pulses remain underutilized and neglected despite showing steady but modest yield increases and adaptation to environments, suggesting that they are better positioned to respond to the diverse needs of smallholder farmers in SSA. In the context of climate change, rain-fed agriculture, depleted agricultural soils, and lack of subsidized fertilizers, there is need to transform existing food systems towards sustainable food production and improved resilience. Increasing pulse agrobiodiversity by integrating long-life cycle pulses in existing farming systems could not only contribute in alleviating malnutrition, but also poverty and inequalities. In addition, representative and accurate data are needed based on the correct use of accepted scientific names for all data across the food system. This is a prerequisite for assessing pulse consumption adequacy and quantifying production and consumption trends.